“Comparative Evaluation of Nutritional Status of Shortened Dental Arch Patients With Completely Dentulous Patients Using Mini Nutritional Assessment- Short Form” - A Cross- Sectional Study - Agrawal, Shanvi (International Journal of Psychosocial Rehabilitation, 2020)
Objective: There are various people having dental arches with edentulous areas which are unrestored and are present posterior to the natural remaining teeth. Such people are known to have a SDA or Shortened Dental Arch . Individuals having SDA may consume a limited diet, containing highly processed& soft foods which can aggravate the possibility of obesity. In this study, we willevaluate the difference in the nutritional status of the patient with SDA as compared to completely dentulous patients and propose a desired intervention for such patients. Methods: This study will be carried out at “Department of Prosthodontics, Sharad Pawar Dental College, Sawangi (Meghe) DMIMS DU, Wardha”. Total 40 patients reporting to OPD with unrestored edentulous area posterior to natural teeth as well as completely dentulous patients will be included in this study Nutritional assessment using “mini nutritional assessment- short form” is evaluated for every subject and compared. Results:- It is expected that this study would provide difference in the nutritional status of the patient with SDA as compared to completely dentulous patients and propose a desired intervention for such patients.